Improving the Accuracy and Fairness of Pretrial Release Decisions: A Multi-Site Study of Risk Assessments Implemented in Four Counties, Indiana, 2015-2018 - Lowder, Evan M. ([Verlag nicht ermittelbar], 2021)
This study was a multi-site, quasi-experimental investigation of risk assessment-informed pretrial release decisions relative to decisions made without risk assessments. The study objectives were to investigate whether use of pretrial risk assessments: 1) improved risk management decisions relative to practice as usual; 2) improved the fairness of pretrial release decisions for racial minorities relative to practice as usual; and 3) revealed judge-level variation in pretrial release decisions. Secondary, administrative data were gathered from four counties in Indiana. Apart from risk assessment information, all data represent public records: court, jail and prison. Variables gathered from the data sources fall into three main categories: defendant variables, pretrial release decisions, and pretrial misconduct outcomes. Examples of specific variables include: booking and release dates, bond amounts, number and type of charges, and demographic information (age, sex and race).